The role of HR practices, big data analytics and innovation in fostering supply chain risk resilience and organizational sustainability - Aljuaid, Abdulrahman Awadh; Alqahtani, Faisal Saad; Albarakati, Sultan Ahmed Mohammed; Alomari, Yazeed Abdullah (International Journal of Economics, Business and Management Studies, 2024)
This study explores the factors influencing logistics firms’ risk resilience during crisis periods, with a focus on HR practices, big data analytics capabilities, and innovation. The research further examines the moderating role of disruptive events in the relationship between risk resilience and organizational sustainability. A quantitative research design was employed, utilizing data collected from 156 employees through a structured questionnaire. The findings demonstrate that the proposed framework has significant predictive capability, with Q² values of 36.6% for risk resilience and 41% for organizational sustainability. The analysis highlights that HR practices, employee development, big data analytics talent and management capabilities, and innovation collectively explain 52.3% of the variance in supply chain risk resilience. Moreover, the combined effect of risk resilience and responses to disruptive events accounts for 55% of the variance in organizational sustainability. These findings emphasize the importance of prioritizing data analytics talent development, effective HR practices, and proactive response strategies to enhance the risk resilience and sustainability of logistics firms. Practical implications suggest that policymakers and industry leaders should focus on improving these critical factors to better navigate challenges posed by crises and disruptive events. This research contributes novel insights into the determinants of supply chain risk resilience and organizational sustainability, offering a valuable framework for strengthening the logistics sector’s adaptability and long-term viability in a dynamic and uncertain business environment.